That's not a daffodil! - Honey, Elizabeth 1947- (Allen & Unwin, 2011)
When Tom's neighbour gives him a brown bulb, he can't believe it will flower. That's not a daffodil, says Tom. Well, says the old gardener. Let's plant it and see
For pre school age
Keywords: Daffodils / Fiction; Children's stories; Narzisse; Blumenzwiebel; Geduld; Gärtner; Junge; Bilderbuch